Pre-referral management of patients with severe preeclampsia and eclampsia in a district hospital, Southeast Sulawesi, Indonesia - Daniel Yoseph Pardomuan; Budi Prasetyo; Rizki Pranadyan (Universitas Airlangga, 2020)
Objective: This study aims to determine the enforcement of diagnosis, management and description of the referral system of PEB and eclampsia patients at Level I Health Facilities and South Konawe Hospital in January-December 2017 Materials and Methods: This study used an observational descriptive design, carried out in the Maternity Room of South Konawe Hospital on 1 January-31 December 2017. There were 47 cases of PEB/Eclampsia from 420 total cases. Most cases of PEB/Eclampsia in Konsel Hospital suffered by pregnant women aged> 35 years, as many as 27 cases (59%). age 21- 34 years, 15 (31%) and the lowest among women aged <20 years, as many as 5 cases (10%). Multigravida, which is 38 cases (81%) and 9 cases 19%) in primigravida. Pregnancy> 34 weeks is 46 cases (98%) and 1 case (2%) at <34 weeks gestation. There were 39 referral cases (83%) all of which were counseled and 8 non-referral cases (17%), where completeness of the tools, medicines and referral letters obtained 39 cases (100%) incomplete. Results: The administration of antihypertensive drugs was given to 89% of cases, and MgSO4 was not given to 100% of cases of PEB/Eclampsia referred to RSUD Konawe Selatan due to fear of officers in providing such therapy to PEB/Eclampsia patients. Examination of urine protein as a support for PEB/Eclampsia cases was recorded in 69% of referral cases at the Konawe Selatan General Hospital. Conclusion: From the whole data, it was found that the pre-requisite conditions had not been fulfilled properly. Referral should be well prepared in order to achieve patient safety and decrease in MMR.